Perancangan Model Proses Bisnis dan Penyusunan Standar Operasinal Prosedur pada PT Promedika Mitra Utama Samarinda - Muhammad Alfiannur Al; Dwi Arief Prambudi; Dwi Nur Amalia (Jurnal Teknologi dan Manajemen, 2023)
Business processes are activities that must be carried out in a company to achieve company goals. Business processes are run by all employees in a company. PT Promedika Mitra Utama Samarinda is a company engaged in the procurement/distribution of hospital medical equipment, personal use, laboratory equipment, HSE safety equipment, and dentistry. Based on the results of interviews with the general manager of PT Promedika Mitra Utama that PT Promedika Mitra Utama does not have business processes and standard operating procedure documents, causing overlapping business processes, employees are less focused on their duties and obligations so that the company's performance and performance are not optimal. The purpose of this research is to design a business process model and develop standard operating procedures at PT Promedika Mitra Utama. The approach used in this research is Business Process Management which has several stages, namely process identification, process discovery, process analysis, and process redesign. In process identification, identification of the required processes and documents owned by PT Promedika Mitra Utama is carried out using several approaches. Process discovery is carried out to collect the business processes carried out and model the business processes using the bizagi application. Process analysis is carried out to analyze the business processes that have been obtained and delete some business processes so that the business processes are of high quality and can be compiled into good standard operating procedures. Process redesign is carried out to improve the business process that has been modeled. Next, the business process improvement is verified by the process owner, namely the General Manager of PT Promedika Mitra Utama Samarinda. After being verified, the SOP is prepared based on the business process that has been modeled and verified by the process owner. This research resulted in 43 business processes and 43 SOPs that can be used by PT Promedika Mitra Utama as a guide for any activities carried out at PT Promedika Mitra Utama